Elemental depth profiles and plasma etching rates of positive-tone electron beam resists after sequential infiltration synthesis of alumina. (2nd May 2018) - Ozaki, Yuki; Ito, Shunya; Hiroshiba, Nobuya; Nakamura, Takahiro; Nakagawa, Masaru
Abstract: By scanning transmission electron microscopy and energy dispersive X-ray spectroscopy (STEM–EDS), we investigated the elemental depth profiles of organic electron beam resist films after the sequential infiltration synthesis (SIS) of inorganic alumina. Although a 40-nm-thick poly(methyl methacrylate) (PMMA) film was entirely hybridized with alumina, an uneven distribution was observed near the interface between the substrate and the resist as well as near the resist surface. The uneven distribution was observed around the center of a 100-nm-thick PMMA film. The thicknesses of the PMMA and CSAR62 resist films decreased almost linearly as functions of plasma etching period. The comparison of etching rate among oxygen reactive ion etching, C3 F8 reactive ion beam etching (RIBE), and Ar ion beam milling suggested that the SIS treatment enhanced the etching resistance of the electron beam resists to chemical reactions rather than to ion collisions. We proposed oxygen- and Ar-assisted C3 F8 RIBE for the fabrication of silica imprint molds by electron beam lithography.